KOMUNIKASI PARIWISATA DALAM PENGEMBANGAN OBJEK WISATA PANTAI OLEH POKDARWIS DI DESA TANJUNG PUNAK KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS - Indra Mulia Perjhaya; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tourism is very popular with all people including parents because by traveling, everyone gets their own satisfaction and comfort. The beach is a tourist destination that is suitable for recreation with family, for that it is necessary for groups to develop coastal attractions. Pokdarwis or Tourism Awareness Group formed by the government aims to develop and explore the tourist destinations of Tanjung Lapin Beach. Pokdarwis carries out its duties in accordance with government regulation number 10 of 2009 concerning developing tourism. This study aims to determine the development of Tanjung Lapin Beach Tourism Objects supported by Pokdarwis, to find out the tourism communication strategies carried out by Pokdarwis and government communication in empowering Pokdarwis. This study used qualitative research methods. The research subjects were five people selected using purposive techniques, informants in this study were three people from Tanjung Punak Village Office North Rupat District, Tourism Awareness Group and from the adat institution Tanjung Punak Village Rupat Utara District, Tourism Office, culture , youth and sports as well as from the community as supporting informants. Data collection is done through interviews, observation and documentation. Data analysis techniques by reducing data, collecting data, presenting data, drawing conclusions and evaluations using the technique of checking the validity of the data, namely the extension of participation and triangulation. The results of this study indicate that the tourism communication strategy of Tanjung Lapin Beach, Tanjung Punak Village, North Rupat Subdistrict, Bengkalis Regency, is to make people aware of the importance of maintaining and cleaning the natural environment around the coast, socializing coastal destinations, making tourism objects superior in North Rupat and developing processed snacks. Tanjung Punak as a tourist souvenir, and use the media as a place for tourism promotion. Empowerment carried out by the Regional Government of the Bengkalis Regency Tourism, Culture, Youth and Sports Office by conducting training, fostering Pokdarwis, taking on the role of beach owner, hiring beach cleaners and promoting the beach through websites and social media.